2019
DOI: 10.1002/cplu.201900192
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Ionic Liquid/Aromatic Systems from NMR Spectroscopy: How Water Affects Solubility and Intermolecular Interactions

Abstract: Hydrocarbon solubility and chemical interactions in ten imidazolium‐ and pyridinium‐based ionic liquids (ILs) with four different anions (thiocyanate [SCN]−, dicyanamide [DCA]−, tricyanomethanide [TCM]−, and bis(trifuoromethylsulfonyl)imide [NTf2]−) have been studied by 1H and 13C NMR spectroscopy. The anion structure has the main influence on the anion–aromatic chemical interaction strength; it is directly correlated to the NMR chemical shift deviations but not to the hydrocarbon solubility. The [TCM]− anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…The molar solubility of the aromatics was calculated from the integral ratio of the aromatic protons and the methyl protons of each IL. , The trend in aromatic solubilities was the same in all three ILs: benzene > toluene > o -xylene > p -xylene ∼ m -xylene > mesitylene (Figure ). This is the same trend observed in other LC systems published in the literature. , Here, we observe a marked difference in the solubility of mesitylene, which is 50–80% lower than benzene in all three ILs. It is unclear whether this trend is a result of electronic or steric effects.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The molar solubility of the aromatics was calculated from the integral ratio of the aromatic protons and the methyl protons of each IL. , The trend in aromatic solubilities was the same in all three ILs: benzene > toluene > o -xylene > p -xylene ∼ m -xylene > mesitylene (Figure ). This is the same trend observed in other LC systems published in the literature. , Here, we observe a marked difference in the solubility of mesitylene, which is 50–80% lower than benzene in all three ILs. It is unclear whether this trend is a result of electronic or steric effects.…”
Section: Resultssupporting
confidence: 92%
“…Our study of the solubilities of a range of aromatic solvents in [HN 222 ]­[Al 2 Cl 7 ], [N 2222 ]­[Al 2 Cl 7 ], and [HN 222 ]­[AlCl 4 ] IL-based LCs, and the subsequent crystallographic and spectroscopic characterization, revealed interesting trends which suggest specific cation/aromatic interactions and anion speciation. The molar solubilities of the aromatic solvents in all three ILs were found to be benzene > toluene > o -xylene > p -xylene ∼ m -xylene > mesitylene, in agreement with the literature; , however, the solubilities in the [AlCl 4 ] − IL were 40–70% lower than those found for the two [Al 2 Cl 7 ] − ILs, which were nearly equivalent. Attempts to crystallize solvates of the aromatics from the six [N 2222 ]­[Al 2 Cl 7 ]/aromatic LCs led to the formation of crystals of [N 2222 ]­[Al 2 Cl 7 ]·C 6 H 6 from benzene but only to crystals of [N 2222 ]­[AlCl 4 ] from the other five aromatic systems, indicating disproportionation of the anion.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ventura et al [27] determined that the aromatic structure of the imidazolium and pyridinium cations increased the toxicity, compared to those ionic liquids based on non-aromatic cations, such as piperidinium or pyrrolidinium cations. In the present work, the more remarkable aromatic nature of the pyridinium cations leads to higher toxicity than that of the imidazolium cations, as the former presents a high-density electron cloud similar to that of the aromatic hydrocarbons meanwhile the aromatic structure of the latter is mainly due to the lone pair of the nitrogen [40]. Figure 3 represents the effect of the cation alkyl chain length on the ecotoxicity.…”
Section: Cation Effect On Ionic Liquids Ecotoxicitymentioning
confidence: 67%
“…Cations play a more important role than anions in the ionic liquid toxicity and the effect of cations overcomes the effect of anions for long alkyl chains; for the [ Couling et al [39] reported that the toxicity of ionic liquids decreases with the increase of localized charges on cations or anions and increases with the presence of positively charged atoms on anions. The localization of the positive charge on the cyano-based ionic liquids depends on the number of nitrogen atoms or cyano-groups in the structure; the [SCN] anion has the highest electron density and one cyano-group while the [TCM] anion the lowest electron density as the negative charge of the [TCM] anion is shared with three -CN groups [40]. Therefore, the more delocalized charge on [TCM] anions and the more numerous regions of positive charge increase its toxicity, compared to [DCA] and [SCN] anions.…”
Section: Resultsmentioning
confidence: 99%